Pengaruh Pariwisata Ikan Sakti Sungai Jernih Terhadap Pengembangan Ekowisata Lokal - Sumiarti, Elni; Yuanita, Ika (CV. ITTC INDONESIA, 2024)
Tourism is one sector that is growing rapidly in its contribution to local economic growth. This study aims to explore the influence of